Liolaemus goetschi (Iguania: Liolaemidae): redescription and phylogenetic relationships within the L. boulengeri group - Nori, Javier (2010)
The genus Liolaemus is a widely distributed and very diverse natural group of lizards. The L. boulengeri group is characterized by the presence of a patch of enlarged scales on the posterior medial surface of the thigh. Liolaemus goetschi, which belongs to this group, was described by Müller and Hellmich in 1938 based on few specimens collected from Laguna Playa (Río Negro Province, Argentina). Those specimens were deposited in museums in Munich(Germany) and Breslau (Poland). The type material of L. goetschi deposited in Poland was lost and because the material in Germany is of difficult access, many populatios of other species have been confused with L. goetschi in subsequent works. In this work, L. goetschi was redescribed by using the characters currently designated for the group and the known distribution of the species was extended. The taxonomic status and phylogenetic relationships of L. goetschi within the L. boulengeri clade was also analyzed, especially with respect to L. melanops and L. martorii.